Synthesis and in vitro Evaluation of ADAM10 and ADAM17 Highly Selective Bioimaging Probes. (12th September 2018) - Camodeca, Caterina; Nuti, Elisa; Tosetti, Francesca; Poggi, Alessandro; D'Arrigo, Cristina; Zocchi, Maria Raffaella; Rossello, Armando
Abstract: A d isintegrina ndm etalloproteinase (ADAMs) are membrane‐bound metalloproteases responsible for the ectodomain shedding of various transmembrane proteins and play important roles in multiple relevant biological processes. Their altered expression is involved in several pathological conditions, and in particular ADAM10 or ADAM17 overexpression is found in various forms of cancer. To better understand how they are regulated in the cellular context, it is useful to visualize the specific ADAMs pathway by means of molecular imaging techniques. For this purpose, we synthesized bioactive fluorescent probes suitable for cell imaging and that are able to specifically target ADAM10 or ADAM17. Two previously developed ADAM17‐ and ADAM10‐selective inhibitors were chosen for conjugation, respectively, to a Cy5.5 dye and to Cy5.5 and FITC dyes. Herein we also report the synthesis of a gold‐labeled compound as an additional bioimaging probe for ADAM10. The newly synthesized ligands were found to be active in vitro on human recombinant ADAM10 and/or ADAM17, showing IC50 values in the nanomolar range and a good selectivity over matrix metalloproteinases (MMPs). Finally, these newly developed probes were successfully used for ADAMs staining on different lymphoma cell lines and lymph node mesenchymal stromal cells. Abstract : Selective ADAM staining : New bioactive probes suitable for cell imaging, able to specifically target ADAM10 or ADAM17, were developed. They were prepared by conjugating ADAM17‐ or ADAM10‐selective inhibitors with Cy5.5 or FITC dyes, or with a gold‐labeled derivative. All these probes were found to be potent and selective for their target and were successfully used for staining of ADAMs on lymphoma cell lines and lymph node stromal cells.